al-Furȗq fî al-Mȗrfîmât bayn al-‘Arabiyyah wa al-Injilîziyyah “al-Mȗrfîm (Mâ) al-‘Arabiy wa al-Injilîziy (what) Anmȗdhajan - Lubna Farah Khan; Nuril Mufidah (The Arabic Education Department Postgraduate Programs, UIN Sultan Maulana Hasanuddin Banten in Partnership with PPJKBA Indonesia, 2021)
This paper investigates Arabic and English morphemes with to identifying the similarities and differences between them. The differences between the two languages might be the main reason for making errors by Arab learners. It might help both teachers and learners to overcome these problems. By identifying the morphological differences between the two languages, teachers will determine how and what to teach, on the one hand, and students will know how and what to focus on when learning the target language, on the other. The Paper will shed light on phonological terms such as: